2001
DOI: 10.1042/bj3590661
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-directed cross-linking localizes regions of the human erythrocyte anion-exchange protein (AE1) relative to the dimeric interface

Abstract: The human erythrocyte anion-exchanger isoform 1 (AE1) is a dimeric membrane protein that exchanges chloride for bicarbonate across the erythrocyte plasma membrane. Crystallographic studies suggest that the transmembrane anion channel lies at the interface between the two monomers, whereas kinetic analysis provides evidence that each monomer contains an anion channel. We have studied the structure-function relationship of residues at the dimeric interface of AE1 by cysteine-directed cross-linking. Single cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Similar discrepancies have been observed for other proteins. In human erythrocyte anion exchange protein (Taylor et al, 2001), for example, only oxidation crosslinking or maleimide cross-linking was observed for some Cys pairs. The differences were interpreted in terms of the dynamics of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar discrepancies have been observed for other proteins. In human erythrocyte anion exchange protein (Taylor et al, 2001), for example, only oxidation crosslinking or maleimide cross-linking was observed for some Cys pairs. The differences were interpreted in terms of the dynamics of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking of Cys in either the signal anchor/linker or F-G loop regions resulted in covalently linked dimers of the 2C8 proteins. Considering the reported efficiency of cross-linking, which ranged from 25 to 80% for different Cys pairs in the human erythrocyte anion exchange protein (Taylor et al, 2001), a substantial fraction of CYP2C8 is likely to exist as a dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine-scanning mutagenesis also favored this orientation (37). However, in this domain, Lys 743 was shown to be accessible from the extracellular side or intracellular side depending on the kind of experiments (38,39). Kanki et al (40) have proposed an explanation to these contradictory observations, and they concluded that during synthesis this region is accessible from the extracellular side, and it is later occluded within the AE1 molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, the conformational alterations within the AE1 SAO/wild-type heterodimer, detectable in ovalocytes as increased protease sensitivity and increased access to surface biotinylation (46), do not reduce detectably the efficiency of AE1 SAO-mediated rescue of Cl Ϫ /HCO 3 Ϫ exchange by AE1 LDAAA in Xenopus oocytes. Taylor et al (58) have documented inter-protomeric cross-linking between identical introduced cysteine residues in the Nterminal-most four exofacial loops connecting AE1 transmembrane spans, as well as less extensive cross-linking at the fifth (possibly re-entrant) exofacial loop. However, aa 821 in another candidate re-entrant loop, and aa 855 in the C-terminal-most external loop, were not subject to cross-linking, consistent with an earlier model of the AE1 homodimer (59) and with chemical cross-linking of the related AE2 anion exchanger (60).…”
Section: Interprotomeric Rescue Of Ae1-mediated Hcomentioning
confidence: 99%